Effects of cognitive demands on attention orientation in L2 oral production. (October 2015) - Fukuta, Junya; Yamashita, Junko
Abstract: In the field of second language (L2) acquisition research, the importance of attention to language form has been supported by many researchers. The Task is a critical concept in the field because its features affect L2 learners' attention orientation in L2 performance. This study explored the ways in which two types of cognitive demands (reasoning demand and dual-task demand) influenced the occurrence and orientation of attention in L2 oral production. This was done by analyzing performance scores (accuracy, complexity, and fluency) and verbal protocols (indicators of attention to lexis, syntax, and phonology). The limited-resource model and the multiple-resource model provided theoretical frameworks for this study. The reasoning demand increased accuracy scores, but the dual-task demand did not. Both types of task demands reduced fluency scores, but no effects were found on complexity scores. The verbal protocol analysis suggested that task demands inhibited learners' attention to syntactic encoding. Overall, the results support the limited-resource model, at least in the monologic task condition employed in this study, leading to the suggestion that task demands may need to be eased to help direct learners' attention to linguistic form and thus enhance L2 acquisition.